<span>6x^2 + 4x = 2x(3x + 2)
4x^2 + 11x + 6 = (4x + 3)(x + 2)
9x^2 - 4 = (3x +2)(3x - 2)</span>
Answer:
y = -3(x + 1)² + 9
Step-by-step explanation:
y = a(x - h)² + k, where (h, k) is the vertex
The vertex of the quadratic function is (-1, 9)
The only equation listed that has a vertex at (-1, 9) is:
y = -3(x + 1)² + 9
Answer:
About an hour, 56 mins.
Step-by-step explanation:
18+18=36
36+20=56
Voila!
(n-5)+45
<span>where n is the number, you always take away 5 and you add 45 because that is the first number of the sequence</span>